Cyclooxygenase-2 inhibitors: promise or peril? - Laurel J. Mengle-Gaw; Benjamin D. Schwartz (Mediators of Inflammation)
The discovery of two isoforms of the cyclooxygenase enzyme, COX-1 and COX-2, and the development of COX-2-specific inhibitors as anti-inflammatories and analgesics have offered great promise that the therapeutic benefits of NSAIDs could be optimized through inhibition of COX-2, while minimizing their adverse side effect profile associated with inhibition of COX-1. While COX-2 specific inhibitors have proven to be efficacious in a variety of inflammatory conditions, exposure of large numbers of patients to these drugs in postmarketing studies have uncovered potential safety concerns that raise questions about the benefit/risk ratio of COX-2-specific NSAIDs compared to conventional NSAIDs. This article reviews the efficacy and safety profiles of COX-2-specific inhibitors, comparing them with conventional NSDAIDs.